Bankruptcy's Effect on Product Identification in Asbestos Personal Injury Cases - Dixon, Lloyd (RAND Corporation, 2015)
This report investigates whether bankruptcy reduces the likelihood that exposure to the asbestos-containing products of bankrupt parties will be identified in interrogatories and depositions. It also presents plaintiff and defense perspectives on whether the findings are a cause for concern and what, if anything, should be done in response.